2013
DOI: 10.1246/cl.130370
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose–Sulfonic Acid: An Efficient, Recyclable, and Biodegradable Solid Acid Catalyst for the Synthesis of 3-Aminoalkylindoles

Abstract: Three-component coupling (3CC) of indoles, aldehydes, and N-alkylanilines has been accomplished using a catalytic amount of cellulose–sulfonic acid under mild reaction conditions to furnish the 3-aminoalkylindoles at room temperature in short reaction times and in relatively good to excellent yields and selectivity. The use of biodegradable cellulose–sulfonic acid makes this method quite simple, convenient, and economically viable for the synthesis of 3-aminoalkylindoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Thus, is not surprising that also different supported sulfonic acids-based catalysts have been developed in the last years, including Fe 3 O 4 -OSO 3 H nanoparticles 98 and cellulose-based sulfonic acid. 99 The main advantage of the first methodology is indeed the possible catalyst recovery using a magnetic stick. Notably, the use of Fe 3 O 4 nanoparticles or sulfonic acids alone favoured the formation of the bis-indolyl by-product, while the use Fe 3 O 4 -OSO 3 H nanoparticles guaranteed the perfect combination of a Lewis and a Brønsted acid, promoting the formation of the mono-alkylated product.…”
Section: Scheme 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, is not surprising that also different supported sulfonic acids-based catalysts have been developed in the last years, including Fe 3 O 4 -OSO 3 H nanoparticles 98 and cellulose-based sulfonic acid. 99 The main advantage of the first methodology is indeed the possible catalyst recovery using a magnetic stick. Notably, the use of Fe 3 O 4 nanoparticles or sulfonic acids alone favoured the formation of the bis-indolyl by-product, while the use Fe 3 O 4 -OSO 3 H nanoparticles guaranteed the perfect combination of a Lewis and a Brønsted acid, promoting the formation of the mono-alkylated product.…”
Section: Scheme 24mentioning
confidence: 99%
“…On the other hand, the cellulose-based catalyst is biodegradable, stable to air, water, and light and is easily recoverable and reusable up to four times. 99 From the first catalysts screening, cellulose-SO 3 H emerged as the most promising to promote the one-pot, three-component reaction between indoles, N-alkyl anilines and aromatic aldehydes. Other metal-based and metal-free Lewis acids resulted the less efficient.…”
Section: Scheme 24mentioning
confidence: 99%
“…70 Similarly, for 3-amino alkylated indoles, recent reported methodologies include l -proline, 71 SDS, 72 iron( iii ) phosphate, 73 β-cyclodextrin, 74 PMA–SiO 2 , 75 silver triflate, 76 bromodimethylsulfonium bromide (BDMS), 77 PANI-HBF 4 , 78 ZrOCl 2 ·2H 2 O/CuCl 2 ·3H 2 O, 79 RGO/ZnO, 80 and cellulose sulfonic acid. 81 However, many of these methodologies are accompanied by several drawbacks such as expensive catalysts, usage of hazardous organic solvents, high temperatures, prolonged reaction times, huge organic waste, low product yield, and difficulty in the recovery and reuse of catalysts. In 2014, He et al and Rawat et al reported the catalyst-free synthesis of 3-amino alkylated indoles.…”
Section: Introductionmentioning
confidence: 99%